The Influence of Money Supply (M2), Interest Rates (r), and Inflation (I) on Indonesia's Economic Growth: A Study During the COVID-19 Pandemic Period (2020–2022) - Muhammad Subryanto (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
This study aims to determine the partial and simultaneous or partial influence of the amount of money in circulation (JUB), interest rates (r) and inflation (I) on Indonesia's economic growth : a study on SARS, Bird Flu (H5N1) and Covid-19 Period 20 1 0-2022 and analyze the policies set by Bank Indonesia when SARS, Bird Flu (H5N1) and Covid-19 occurred . This type of research uses quantitative descriptive research, namely research that provides an overview of the influence of the amount of money in circulation (JUB), interest rates (r) and inflation (I) on Indonesia's economic growth: a study on SARS, Bird Flu (H5N1) and Covid-19 Period 2010-2022 This research was conducted in Indonesia because it is a country that is directly affected by the SARS, Bird Flu and Covid-19 viruses which have an impact on economic development in the last ten years. The research process includes several stages, namely, the preparation of research proposals which are divided into compiling research proposals, implementing research which is divided into the interview process, as well as analysis, data processing, and writing research reports. In this study, the objects of research are the amount of money in circulation, interest rates and inflation as independent variables and economic growth as the dependent variable . The results of this study show that the variables of Money Supply, Interest Rates, and Inflation have a significant effect on economic growth. The results of this analysis indicate that BI's monetary policy, especially in managing the amount of money in circulation and interest rates, plays an important role in maintaining economic stability and encouraging economic growth during the Covid-19 pandemic period 2020-2022